Pengaruh Kualitas Produk Dan Inovasi Terhadap Keputusan Pembelian Pada Defitex.Id (Survei Pada Konsumen Mukena Travel Defitex.Id) - Muhamad Rafli Nauval; Arga Sutrisna; Titin Patimah (Jurnal Multidisiplin Dehasen (MUDE), 2024)
The aim of this research is to determine and analyze the influence of product quality and innovation on purchasing decisions among mukena travel defitex.id consumers. The research method used in this research is a quantitative method with a survey approach, while the types of data used in this research are primary data and secondary data. The object of this research is product quality, innovation and purchasing decisions among mukena travel defitex.id consumers. The data analysis technique used is multiple linear analysis and hypothesis testing in the form of the F test and t test. The results of this test prove that product quality and innovation simultaneously have a significant influence on purchasing decisions for mukena travel defitex.id consumers. Partially, product quality and innovation have a significant effect on purchasing decisions.